2022
DOI: 10.1039/d2ra04627j
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and the improvement of effective thermal conductivity for a metal hydride bed – a review

Abstract: Solid-state hydrogen storage based on metal hydrides is considered a promising method for hydrogen storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 118 publications
(246 reference statements)
0
1
0
Order By: Relevance
“…The higher average COF value of hydrogen-charged AISI 316H material might be ascribed to the slight local overheating of its tribological surface due to decreased thermal conductivity by the presence of hydrogen. Indeed, it has been reported that for pure metals and alloys, thermal conductivity is reduced due to the insertion of hydrogen atoms, which hinders the thermal conduction of free electrons [59]. Such behavior was also confirmed by Luo et al [60] in their first-principles study dealing with the effect of interstitial hydrogen on the mechanical and thermal properties of tungsten.…”
Section: Effect Of Hydrogen Charging On Tribological Behaviormentioning
confidence: 71%
“…The higher average COF value of hydrogen-charged AISI 316H material might be ascribed to the slight local overheating of its tribological surface due to decreased thermal conductivity by the presence of hydrogen. Indeed, it has been reported that for pure metals and alloys, thermal conductivity is reduced due to the insertion of hydrogen atoms, which hinders the thermal conduction of free electrons [59]. Such behavior was also confirmed by Luo et al [60] in their first-principles study dealing with the effect of interstitial hydrogen on the mechanical and thermal properties of tungsten.…”
Section: Effect Of Hydrogen Charging On Tribological Behaviormentioning
confidence: 71%
“…Enhancing kMH it is indeed possible to guarantee higher pdes thus reducing energy/OPEX spent at this purpose. To enhance MH thermal conductivity different techniques could be pursued: using metallic foams and alloys coupled with MH, reducing MH powder porosity via thermal cycles, create MH alloys with high thermal conductivity metals [25], [26]. Nevertheless, usually, an increase of kMH entails a reduction in the gravimetric/volumetric capacity of metal hydrides.…”
Section: Auxiliary Compressor Weekly Energy Consumptionmentioning
confidence: 99%